Rehabilitation of facial palsy by the lengthening temporalis myoplastie: A case report - Kerdoud, Ouassime (Ann Med Surg (Lond), 2021)
INTRODUCTION: The lengthening temporalis myoplasty (LTM) is defined as a transfer of the entire temporal muscle from the coronoid process to the labial commissure reinserted into the orbicularis muscle. PRESENTATION OF CASE: a 60-year-old man with grade III longstanding facial paralysis of the right hemi-face secondary to a right total parotidectomy. The surgery was performed for the rehabilitation of the right hemi-facial side by the lengthening temporalis myoplasty. The follow-up was favorable with improvement of the facial dynamics. DISCUSSION: Surgical management of the longstanding facial palsy is a real challenge. The lengthening temporalis myoplasty offers several advantages; technically is a simple. This technique was demonstrated in severe neglected facial palsy and is performed when there is a definitive complete, or almost complete, loss of the facial nerve and the trigeminal is preserved. Effective rehabilitation through training and physical therapy is necessary to optimize results. CONCLUSION: Facial palsy should no longer be permanent, surgical techniques as lengthening temporalis myoplasty with early postoperative physiotherapy leads to good results. Preoperative planning and early recognition of issues can avoid postoperative complications.